Patients Refusing Prehospital Transport Are Increasingly Likely to Be Geriatric - Peyton Holder (Emergency Medicine International, 2012)
Objective. Elderly patients are becoming an increasingly larger proportion of our population, and there is a paucity of data regarding the epidemiology of geriatric patients refusing transport. Treatment refusal rates range from 5% to 15% in many studies. This study sought to test the hypothesis that geriatric patients constituted an increasing proportion of those persons refusing prehospital transport. Methods. This study was a retrospective analysis of data from a query of a large urban EMS service. Results. There were a total of 22,347 adult transport refusals recorded during the 16-month study period. Multivariate logistic regression incorporating covariates for sex, race, season, chief complaint, metropolitan region, and whether any treatment occurred prior to transport refusal confirmed the increasing likelihood of Period 2 patients being geriatric, as compared with Period 1 (OR 1.24, 95% CI 1.14–1.35, Wald P<.001). Conclusion. This data shows that despite controlling for these covariates, patients refusing transport in the second period of this study were nearly 25% more likely to be geriatric as compared to those in the initial 8 months of the study.